2020
DOI: 10.3390/polym12122799
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin-Conjugated Iron Oxide Nanoparticles Synthesized by Laser Pyrolysis: In Vitro Study on Human Breast Cancer Cells

Abstract: Even today, breast cancer remains a global public problem, with a high mortality rate among women. Nanoparticle (NP) based systems are developed to enhance drug delivery, reducing the toxic effect of medicine molecules. By using iron oxide nanoparticles for cancer treatment, several advantages were highlighted: the ability to target specific locations derived from their magnetic properties and reduced side effects. The aim of this study was to examine on breast cancer cell line the anticancer potential of γ-Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Several constructions were studied for DOX loading. Among them are gold [45], carbonate [40], iron oxide nanoparticles [21,39,41,42,[47][48][49][50][51][52][53][54][55][56][57][58][59], metal-organic frameworks [60], and much more laborious and complex constructions [61][62][63][64]. However, MNPs in the published works demonstrate only a low noncovalent drug loading capacity (µg/mg, DOX/MNP): 11 [55,56], 22 [57], 50 [42,51,58], 91 [54], 110 [41], 120 [65,66], 131 [50], 300 [53].…”
Section: Introductionmentioning
confidence: 99%
“…Several constructions were studied for DOX loading. Among them are gold [45], carbonate [40], iron oxide nanoparticles [21,39,41,42,[47][48][49][50][51][52][53][54][55][56][57][58][59], metal-organic frameworks [60], and much more laborious and complex constructions [61][62][63][64]. However, MNPs in the published works demonstrate only a low noncovalent drug loading capacity (µg/mg, DOX/MNP): 11 [55,56], 22 [57], 50 [42,51,58], 91 [54], 110 [41], 120 [65,66], 131 [50], 300 [53].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of these bands confirmed that the DOX successfully conjugated with AZnFe-NPs. 50 The bands at 3435 and 1601 cm −1 for the plain SA/CMC mixture (which was used as a placebo in this study) were attributed to stretching vibrations of –COOH and those of O–H and C=O, respectively. In the spectrum of SACMC-DOX, the C=O stretching frequency was shifted to 1597 cm −1 .…”
Section: Resultsmentioning
confidence: 81%
“…This method allows users to quickly obtain product, and the yield was quite considerable as well. Furthermore, the method was easy and required no sophisticated instruments compared to other methods [ 30 ]. The HO@Fe 3 O 4 was then modified with an amine group and further polymerization of MAA and NIPAM through RAFT polymerization.…”
Section: Discussionmentioning
confidence: 99%